2014
DOI: 10.1080/15339114.2014.927747
|View full text |Cite
|
Sign up to set email alerts
|

Property Prices and Housing Affordability in China: A Regional Comparison

Abstract: This study explores two issues related to China's property market dynamics. First, it examines how regional property price disparity is caused by space and capital market differentials, based on the Four-Quadrant Framework. With the panel data fixed effect model of 35 major cities from 2002 to 2012, it integrates regional factors, or the economic and demographic conditions in Quadrant I, into the Four-Quadrant framework. The empirical results suggest that in the coastal cities the capital market plays a bigger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The increasing total number of cities having housing bubbles from 2014 to 2016 may be due to the relaxation of home purchase quota in China (Li & Xu, 2016). Previous studies have demonstrated that cities in the eastern region have more housing pressures than those in the western regions, due to the demographic clustering effect for the coastal regions and the hollowing-out effect for the inland regions' population movement (Li, Xu, & Chiang, 2014;Choy & Li, 2017). The findings also echo previous literature that eastern regions have more severe housing bubbles (Dreger & Zhang, 2013).…”
Section: Discussion Of Resultssupporting
confidence: 74%
“…The increasing total number of cities having housing bubbles from 2014 to 2016 may be due to the relaxation of home purchase quota in China (Li & Xu, 2016). Previous studies have demonstrated that cities in the eastern region have more housing pressures than those in the western regions, due to the demographic clustering effect for the coastal regions and the hollowing-out effect for the inland regions' population movement (Li, Xu, & Chiang, 2014;Choy & Li, 2017). The findings also echo previous literature that eastern regions have more severe housing bubbles (Dreger & Zhang, 2013).…”
Section: Discussion Of Resultssupporting
confidence: 74%
“…Results detect that HP do Granger cause the MR in the Central region. It is an agricultural and populated province, the origin of migrant to the first-tier provinces (Li et al, 2014). Henan is one of the provinces where extravagant spending has incurred on MR. As compared to the national level, the average income is lower, and some people borrow to get married.…”
Section: Data and Empirical Resultsmentioning
confidence: 99%
“…Li and Chand (2013) state that MR contributes a significant part in the housing demand and without housing, marriage is considered incomplete. Li et al (2014) analyze the property prices and housing affordability and reveal that homeownership is prerequisite of MR. Yu and Xie (2015) detect that higher HP is associated with early entry into MR and vice versa. Li and Song (2016) have explored the nexus between HP and MR on the country level and has ignored the regional dimension which may vary across the different regions.…”
mentioning
confidence: 99%
“…Wei et al (2012) address the perceived status symbol of housing and its significant role in attracting a partner for MR. Li and Chand (2013) show that MR is a meaningful factor in housing demand and is considered incomplete without housing. Li et al (2014) inspect housing prices and affordability and find that homeownership is necessary for MR. Yu and Xie (2015) find that higher HPs are associated with early entry into MR and vice versa. Li and Song (2016) discuss the different reasons, including economic, social and cultural, for the dramatic increase in HPs and the decline in housing affordability.…”
Section: Literature Reviewmentioning
confidence: 99%